Ladies Parking: Pengalaman Pengguna Ruang Parkir Khusus Perempuan di Kota Makassar - Azizah, Andi Jihan (Universitas Muslim Maros, 2025)
Ladies parking is a women-only parking facility introduced to improve the safety and comfort of female users. Many countries around the world have implemented this facility, including Indonesia. In Makassar, women-only parking faces various challenges in its implementation that affect the users’ experience. This article focuses on the user experience and obstacles encountered in the implementation of ladies parking in the city of Makassar. This research using a qualitative approach was conducted in three shopping centers in Makassar, namely Panakkukang Mall, Nipah Mall and Ratu Indah Mall. This study involved 13 informants who varied based on gender consisting of six women and seven men, age (between 21 and 53 years), job (college students, private employees, housewives, parking attendant, and lecturer) and status (users, intruders, parking attendants and observers). In-depth interview and observation are two data collection methods employed in this study. The findings of this study show that the experience of users of ladies parking facilities in the city of Makassar is divided between satisfaction and disappointment. While the first can be seen from the joy of female users because this facility helps to make ease to get a parking space. On the other hand, female users feel disappointed since many parking users ignore the ladies parking rules. This is a challenge in itself in optimizing the existence of this particular facility for women. Ladies parking cannot be optimized due to a number of obstacles, namely: the male intrusion into ladies parking who see parking area is for everybody regardless of their gender, the non-compliance of male drivers with rude responses, weak supervision in the ladies parking area, and limited space for the ladies parking. Non-compliance with special parking for women is usually followed by a debate related to equality in parking lots, that anyone can park anywhere, men or women and this hinders the provision of particular parking lots for women. The experience of the users of this facility also shows the need for improvement in supervision and rule enforcement to optimize the implementation of ladies parking in order to provide comfort and security for female drivers.